Automatic pre-bended customized prosthesis for pectus excavatum minimal invasive surgery correction - Vilaça, João L. (2013)
Pectus excavatum is the most common deformity of the thorax. A minimally invasive surgical correction is commonly carried out to remodel the anterior chest wall, by employing an intrathoracic convex prosthesis in substernal position. The process of prosthesis modeling and bending still remains an area of improvement. The authors developed a new system, i3DExcavatum, which can automatically model and bend the bar preoperatively based on a thoracic CT-scan. This paper presents a comparison between automatic and manual bending. The i3DExcavatum was used to personalize prosthesis for 41 patients who underwent pectus excavatum surgical correction between 2007 and 2012. Regarding the anatomic variations, the soft tissue thicknesses external to the ribs show that symmetric or asymmetric patients have always asymmetric variations by comparing both patients’ sides. It highlighted that the prosthesis bar should be modeled according to each patient ribs position and dimension. The average differences between the skin and costal line curvature lengths were 84±4 mm and 96±11mm, for male and female patients, respectively. On the other hand, the i3DExcavatum ensured a smooth curvature of the surgical prosthesis and was capable to predict and simulate a virtual shape and size of the bar for asymmetric or symmetric patients. In conclusion, the i3DExcavatum allows preoperative personalization according to the thoracic morphology of each patient. It reduces surgery time and minimizes the margin error induced by the manual bended bar shape that only uses a template that copies the chest wall curvature.